2018
DOI: 10.12659/msm.908548
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Pregnancy Health Status and Risk of Preterm Birth: A Large, Chinese, Rural, Population-Based Study

Abstract: The aim of this study was to estimate the incidence of preterm birth (PTB) and identify maternal risk factors before pregnancy in rural China, and to determine their population-attributable fractions (PAFs).A prospectively population-based study was conducted in the city of Fuyang, China. Surveillance locations were randomly selected by cluster sampling based on administrative areas and geographic characteristics. Data were collected through interview questionnaires and medical examination records from the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“… 10 A prospective study examined the relationship between prepregnancy maternal factors and obstetric outcomes that fasting blood sugar of more than 6.1 mmol/L (108.9 mg/dL) was associated with increased preterm birth after adjustment. 11 Another recent study on prepregnancy IFG was a retrospective cohort study what revealed IFG increased the risk of preterm birth, LGA and severe LGA. 12 …”
Section: Discussionmentioning
confidence: 99%
“… 10 A prospective study examined the relationship between prepregnancy maternal factors and obstetric outcomes that fasting blood sugar of more than 6.1 mmol/L (108.9 mg/dL) was associated with increased preterm birth after adjustment. 11 Another recent study on prepregnancy IFG was a retrospective cohort study what revealed IFG increased the risk of preterm birth, LGA and severe LGA. 12 …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 2 studies among the few studies pertaining to prepregnancy IFG and adverse pregnancy outcomes. 30,31 Salman et al 30 analyzed singleton pregnancies of 1945 women in Israel, but the authors found the association of prepregnancy IFG only with the abnormal glucose challenge test and gestational diabetes mellitus (GDM), rather than with an increased risk of PTB and LGA.…”
Section: Ajogorgmentioning
confidence: 99%
“…Hu et al 31 conducted a prospective study of 16,890 women in central China to estimate the incidence of PTB and identify maternal risk factors before pregnancy from 2010 to 2013. Although they found that women with prepregnancy hyperglycaemia (FBG level >6.1 mmol/L) had an increased risk of PTB compared with women with normoglycaemia (3.9 mmol/L or greater and 6.1 mmol/L or less) after adjustment (6.3% vs 3.6%, aOR, 1.69, 95% CI, 1.09e2.62), the definition of hyperglycemia in this study was unclear, which reduced the strength of the study.…”
Section: Ajogorgmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, we found that autoimmune disease (SLE and APS) increased the risk of PTB < 37 weeks 13 . However, PCOS and hypothyroidism previously associated with PTB were not significantly correlated with occurrence of PTB 18,19 . In the current study, prepregnancy hypertension was associated with PTB < 34 weeks but not PTB < 37 weeks.…”
Section: Discussionmentioning
confidence: 67%